'Never again will I be carefree': a qualitative study of the impact of hypoglycemia on quality of life among adults with type 1 diabetes. Issue 1 (16th August 2021) - Chatwin, Hannah; Broadley, Melanie; Valdersdorf Jensen, Mette; Hendrieckx, Christel; Carlton, Jill; Heller, Simon; Amiel, Stephanie; de Galan, Bastiaan; Hermanns, Norbert; Finke-Groene, Katharina; Speight, Jane; Pouwer, Frans
Abstract : Introduction: Achieving glycemic targets and optimizing quality of life (QoL) are important goals of type 1 diabetes care. Hypoglycemia is a common barrier to achieving targets and can be associated with significant distress. However, the impact of hypoglycemia on QoL is not fully understood. The aim of this study was to explore how adults with type 1 diabetes are impacted by hypoglycemia in areas of life that are important to their overall QoL. Research design and methods: Participants responded to a web-based qualitative survey involving a novel 'Wheel of Life' activity. Responses were analyzed using reflexive thematic analysis. Results: The final sample included 219 adults with type 1 diabetes from Denmark, Germany, the Netherlands, and the UK. They had a mean±SD age of 39±13 years and diabetes duration of 20±14 years. Participants identified eight areas of life important to their overall QoL, including relationships and social life, work and studies, leisure and physical activity, everyday life, sleep, sex life, physical health, and mental health. Participants reported emotional, behavioral, cognitive, and social impacts of hypoglycemia within domains. Across domains, participants described interruptions, limited participation in activities, exhaustion, fear of hypoglycemia, compensatory strategies to prevent hypoglycemia, and reduced spontaneity. Conclusions: The findings emphasize the profound impact of hypoglycemia on QoL and diabetes self-care behaviors. Diabetes services should be aware of and address the burden of hypoglycemia to provide person-centered care. Clinicians could ask individuals how hypoglycemia affects important areas of their lives to better understand the personal impact and develop tailored management plans.